2011
DOI: 10.4161/hv.7.10.16763
|View full text |Cite
|
Sign up to set email alerts
|

Binding activity and immunogenic characterization of recombinant C-terminal quarter and half of the heavy chain of botulinum neurotoxin serotype A

Abstract: (2011) Binding activity and immunogenic characterization of recombinant C-terminal quarter and half of the heavy chain of botulinum neurotoxin serotype A, Human Vaccines, 7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…The efficacy of this type of DNA vaccines against BoNT/A also needs to compare with that of the subunit AHc or toxoid vaccines for future clinical trial or clinical use. 37,38 To our knowledge, this is the first report to date demonstrating the potency of IL-4 as an adjuvant on replicon vaccines in both strain mice. Thus, we described a strategy to design and develop efficient vaccines against BoNT/A or other pathogens using one replicon vector to simultaneously co-express antigen and molecular adjuvant.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The efficacy of this type of DNA vaccines against BoNT/A also needs to compare with that of the subunit AHc or toxoid vaccines for future clinical trial or clinical use. 37,38 To our knowledge, this is the first report to date demonstrating the potency of IL-4 as an adjuvant on replicon vaccines in both strain mice. Thus, we described a strategy to design and develop efficient vaccines against BoNT/A or other pathogens using one replicon vector to simultaneously co-express antigen and molecular adjuvant.…”
Section: Discussionmentioning
confidence: 80%
“…Pooled sera from each group of mice above were diluted initially 1:8 and then 2-fold for serum neutralization titers as described previously. 37,38 Briefly, mixtures of serial dilutions of sera with 100 LD 50 of BoNT/A (L+1/100) between group differences. Fisher's exact test was used to determine statistical differences in survival between the treatment groups.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that genetic fusion of the chemokines MCP-3 and IP-10 to a model self-tumor antigen converts non-immunogenic sFv into a potent immunogen and induces anti-idiotypic antibody responses and protective antitumor immunity [17,22,23]. DNA vaccines encoding gp120 fused with proinflammatory chemoattractants of immature dendritic cells, such as β-defensin 2, monocyte chemoattractant protein-3 (MCP-3) or macrophage-derived chemokine (MDC/ CCL22), elicited anti-gp120 antibodies with high titers of virus-neutralizing activity [19]. A prototype MDC/CCL22-based DNA epitope vaccine expressing a fusion protein was shown to promote a strong anti-inflammatory Th2-polarized humoral immune response in a 3×Tg-AD mouse model [24].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-AHc-C antibodies in the sera from mice in the different groups were detected by ELISA as described previously [19,20]. Briefly, ELISA plates (Corning) were coated overnight at 4°C with 100 μl recombinant AHc-C (2 μg/ml).…”
Section: Detection Of Anti-ahc-c Antibodies In Serummentioning
confidence: 99%
“…35 Briefly, ELISA plates were coated with 100 ml of 40 mg/ ml bovine ganglioside GT1b (Sigma) per well and blocked with PBS containing 1% Casein (Sigma) at 25 C for 3 h. After incubation, 100 ml of purified BHc (50 mg /mL) or BSA (50 mg/ mL) was added to different wells for 3 h at 25 C. Unbound BHc protein was removed by three washes each with PBS containing 0.05% Tween-20 (PBST). Plates were incubated for 8 h at 4 C with 100 ml of 1:2,000 dilutions of polyclonal mouse anti-BHc antibodies, washed, and incubated for 0.5 h with goat antimouse IgG-HRP.…”
Section: Ganglioside Bindingmentioning
confidence: 99%